Towards a successful transition to work - which employability factors contribute to early career success?. Issue 6 (3rd October 2022) - Tuononen, Tarja; Hyytinen, Heidi
ABSTRACT: The transition from university to working life is a challenging phase for graduates. The focus in the present longitudinal study is on employability factors and their association with this transition and with early career success. The participants were 43 graduates who were interviewed at the time of their graduation and filled in a follow-up questionnaire three years later. The data were analysed using qualitative content analysis. The results revealed five employability factors relating early career success: (1) career plans and goals, (2) perceived competences related to the degree, (3) self-efficacy beliefs, (4) activity and (5) work experience and networks. Three transition groups emerged based on the differences in employability factors and career success, which we labelled smooth transition, progressive transition and a rocky road. The results revealed individual variation in employability factors and in the kind of challenges these graduates encountered in the transition phase and in their early career. An awareness of the ways in which graduates differ could help educators to develop practises that better support students and graduates in the transition to working life. These findings highlight the importance of active career planning during one's studies.